Strategies for High Precision Processing of GPS Measurements with Application to the Amery Ice Shelf, East Antarctica - King, MA; Nguyen, LN; Coleman, R; Morgan, PJ (GPS Solutions, 2000)
2000, John Wiley & Sons, Inc. A number of statistic Global Positioning System (GPS) measurement campaigns have been made on a floating Antarctic ice shelf, the Amery Ice Shelf, as part of ongoing glaciological studies designed to investigate the ice shelf dynamics, grounding zone definition, and ice shelf strain. Such studies ar fundamental to improving out knowledge of the Antarctic ice-sheet mass balance and dynamical models of ice sheet/ocean interaction. This article describes two techniques used to process the statistic GPS data. One approach uses a segmented version of the classical static methodology, and the other approach adopts a new sequential processing technique. Both approaches yield similar results for the station coordinates and demonstrate the potential of GPS for extracting the tidal signal on the ice shelves and giving information on the dynamical motion of the ice sheet. To verify our results for the vertical component, we compare the ice shelf GPS tidal signal with a tidal model derived from tide gauge measurements at nearby Beaver Lake. Comparison of the GPS results with the tide model give good agreement in amplitude at the few cm level (GPS results always larger) but clearly shows evidence of phase propagation of the ocean tidal wave under the ice shelf. Improving the resolution of the tides over the ice shelves will be of tremendous benefit for future satellite missions, such as Ice, Cloud and Land Elevation Satellite (ICESAT), and the integrated use of GPS and satellite data will be fundamental for any on-going Antarctic ice sheet mass balance studies. 2000 John Wiley & Sons, Inc.